Processed Oyster Mushrooms (Pleurotus ostreatus) Into Chrispy Mushrooms With Various Flavors As An Effort To Drive MSMEs in Birandang Island - Fadhillah, dkk., Zata (MASPUL JOURNAL OF COMMUNITY EMPOWERMENT, 2022)
Micro, Small and Medium Enterprises (MSMEs), are one of the driving forces for economic development in Indonesia. MSMEs are able to create new jobs so that they can absorb the productive age workforce, and as an effort to increase income. The business of diversifying oyster mushrooms that are processed into crispy oyster mushrooms as a functional food that has a positive impact on people’s health is a trend today. Through the MSME group, Birandang Island Village, Kampar District, Kampar Regency, Riau, it is an opportunity to increase people’s income, utilize agricultural products through processed mushroom products and provide functional food-based food diversity. The purpose of this community service is to help MSME partners in Birandang Island Village in developing diversification of oyster mushroom agricultural products into crispy mushrooms that can increase sales and income. The methods used are surveys, socialization, and training. The results obtained are to produce diversification of processed oyster mushroom products into crispy mushrooms as the latest innovation and add a more economical selling point for MSME activists in Birandang Island Village which is shaded by Bdan Village-Owned Enterprises.